SOS! Summer of Smoke: a retrospective cohort study examining the cardiorespiratory impacts of a severe and prolonged wildfire season in Canada's high subarctic. Issue 2 (4th February 2021) - Howard, Courtney; Rose, Caren; Dodd, Warren; Kohle, Katherine; Scott, Craig; Scott, Patrick; Cunsolo, Ashlee; Orbinski, James
Abstract : Objectives: To determine healthcare service utilisation for cardiorespiratory presentations and outpatient salbutamol dispensation associated with 2.5 months of severe, unabating wildfire smoke in Canada's high subarctic. Design: A retrospective cohort study using hospital, clinic, pharmacy and environmental data analysed using Poisson regression. Setting: Territorial referral hospital and clinics in Yellowknife, Northwest Territories, Canada. Participants: Individuals from Yellowknife and surrounding communities presenting for care between 2012 and 2015. Main outcome measures: Emergency room (ER) presentations, hospital admissions and clinic visits for cardiorespiratory events, and outpatient salbutamol prescriptions Results: The median 24-hour mean particulate matter (PM2.5 ) was fivefold higher in the summer of 2014 compared with 2012, 2013 and 2015 (median=30.8 µg/m 3 ), with the mean peaking at 320.3 µg/m 3 . A 10 µg/m 3 increase in PM2.5 was associated with an increase in asthma-related (incidence rate ratio (IRR) (95% CI): 1.11 (1.07, 1.14)) and pneumonia-related ER visits (IRR (95% CI): 1.06 (1.02, 1.10)), as well as an increase in chronic obstructive pulmonary disease hospitalisations (IRR (95% CI): 1.11 (1.02, 1.20). Compared with 2012 and 2013, salbutamol dispensations in 2014 increased by 48%; clinic visits for asthma, pneumonia and cough increased; ER visits for asthma doubled, with the highest rate in females, in adults aged ≥40 years and in Dene people, while pneumonia increased by 57%, with higher rates in males, in individualsaged <40 years and in Inuit people. Cardiac variables were unchanged. Conclusions: Severe wildfires in 2014 resulted in extended poor air quality associated with increases in health resource utilization; some impacts were seen disproportionately among vulnerable populations, such as children and Indigenous individuals. Public health advisories asking people to stay inside were inadequately protective, with compliance possibly impacted by the prolonged exposure. Future research should investigate use of at-home air filtration systems, clean-air shelters and public health messaging which addresses mental health and supports physical activity.